Introduction to polymer physics - Doi, M. (Masao), 1948- (Oxford : Clarendon Press, 1996)
This book is a concise and clearly written introduction to the modern theory of polymer physics. The book describes basic concepts and methods of investigating the statistical properties of the assembly of chain-like molecules. The topics discussed include scaling theory, concentration fluctuation, gels, and reptation. Both graduate students and researchers in physics, physical chemistry, chemical engineering, and materials science will find this an extremely useful textbook and reference work.
1. Properties of an isolated polymer molecule -- 2. Concentrated solutions and melts -- 3. Polymer gels -- 4. Molecular motion of polymers in dilute solution -- 5. Molecular motion in entangled polymer systems.
Includes bibliographical references (p. [114]-115) and index.
Keywords: Polymers